Effect of surfactant on microstructure, surface hydrophilicity, mechanical and thermal properties of different multi-walled carbon nanotube/polystyrene composites. (23rd May 2018) - Li, Zhipeng; Zhang, Yanxia; Liang, Shaolei; Li, Guangfen
Abstract: We prepared nanocomposites of multi-walled carbon nanotube (MWCNT)/polystyrene via a solution casting method, where deionized water was used as coagulation bath. The influences of the type of MWCNTs and existence of surfactant on surface morphology, thermal properties and mechanical properties of MWCNT/polystyrene composites were extensively investigated. The pristine and two functionalized MWCNTs with the loading of 5 wt% were chosen for comparison. Both scanning electron microscopy and mercury intrusion porosimetry show that the composites without surfactant contain fewer pores and thus have higher bulk density, tensile strength, as well as low surface hydrophobicity. However, the porous structures within micro-range appear in all surfactant-treated composites, which decrease the bulk density and the tensile strength of their composites. This especially pronounced for the MWCNT-OH composite as the smallest pore size/highest porosity is found in the composites with loading of 5 wt% MWCNT-OH due to the higher content of hydroxyl groups. Despite the glass transition temperatures (Tg) of all the surfactant-treated composites lower compared with Tg for pure polystyrene, they increase for MWCNTs and MWCNT-OH composite without surfactant.